An Application of Flipped Classroom in Mathematics Teacher Education Programme - Umam, Khoerul; Nusantara, Toto; Parta, I Nengah; Hidayanto, Erry; Mulyono, Herri (International Journal of Interactive Mobile Technologies (iJIM), 2019)
A body of literature has suggested the benefits of flipped classrooms in mathematics learning at university. However, there is still a lack of evidence regarding the benefits in the context of mathematics teacher education programme. This study aimed to examine the effectiveness of a flipped classroom application in a mathematics teacher education programme at a private university in Indonesia. A total of thirty-one pre-service teachers participated in the study. Multiple data collection methods were employed including observation, written journals and tests. The data were then analysed both quantitatively and qualitatively. The findings showed that flipped classroom promotes independent learning, with the type of classroom encouraging students to work together with other peers and improved learning awareness. However, some challenges were highlighted in flipped classroom application such as technical issues, editing recording skills, and it was time consuming. Recommendations are offered in reference with the findings.